Membangun Kredibilitas Manajemen Pendidikan Dasar Melalui Penerapan Artificial Intelligence, Kompetensi Manajemen, dan Etos Kerja - Nanik Puji Arsanti; Bambang Ismanto; Tita Rosita (Universitas Negeri Padang, 2023)
This research presents several findings regarding the minimal use of artificial intelligence, poor school management and low work ethic. The aim of the research is to analyze the application of artificial intelligence, the quality of management competence, and the work ethic of school principals. The research population was 80 teachers (PNS and non-PNS) at the State Elementary School in the Assisted Region 1, Bojong District, Tegal Regency (Diponegoro Cluster). The sampling technique uses saturated samples, so the number of samples is also 80 teachers. The data analysis technique uses descriptive statistics. The research results are that the application of artificial intelligence is in the medium category. The majority of respondents' choice refers to the pleasure of teaching language subjects using the translation method in the high category. The fewest selected indicators from respondents lead to the use of automatic assessment applications in the medium category. Management quality is in the high category. The most answer choices refer to improving the quality of basic education in the high category. The answers to the questionnaire focused at least on the principal's statement of achievement in the high category. The Principal's work ethic is in the high category. The respondents' most chosen answers lead to statements of truth in speaking and fostering cooperation between teachers and staff in the high category. The respondents' least choice refers to concentration at work in the high category.